Emergence of Plasmid-Borne dfrA14 Trimethoprim Resistance Gene in Shigella sonnei - Miranda, Alfonso; Ávila, Bárbara; Díaz, Patricia; Rivas, Lina; Bravo, Karen; Astudillo, Javier; Bueno, Constanza; Ulloa, María T.; Hermosilla, Germán; Del Canto, Felipe; Salazar, Juan C.; Toro, Cecilia S. (Frontiers in Cellular and Infection Microbiology, 2016)
The most common mechanism of trimethoprim (TMP)-resistance is the acquisition of dihydrofolate reductase enzyme resistant to this drug. Previous molecular characterization of TMP-genes resistance in Chilean isolates of S. sonnei searching for dfrA1 and dfrA8, showed solely the presence of dfrA8 (formerly dhfrIIIc). However, these genetic markers were absent in S. sonnei strains further isolated during an outbreak in 2009. To identify the TMP-resistance gene in these strains, a genomic DNA library from a TMP-resistant (TMPR) S. sonnei representative strain for the outbreak was used to clone, select and identify a TMP-resistance marker. The TMPR clone was sequenced by primer walking, identifying the presence of the dfrA14 gene in the sul2-strA’-dfrA14-‘strA-strB gene arrangement, harbored in a native 6,779-bp plasmid. The same plasmid was isolated by transforming with a 4.2 MDa plasmid extracted from several TMPR S. sonnei strains into E. coli. This plasmid, named pABC-3, was present only in dfrA14-positive strains and was homologous to a previously described pCERC-1, but different due to the absence of an 11-bp repetitive unit. The distribution of dfrA1, dfrA8 and dfrA14 TMP-resistance genes was determined in 126 TMPR S. sonnei isolates. Most of the strains (96 %) carried only one of the three TMP-resistance genes assessed. Thus, all strains obtained during the 2009-outbreak harbored only dfrA14, whereas, dfrA8 was the most abundant gene marker before outbreak and, after the outbreak dfrA1 seems have appeared in circulating strains. According to PFGE, dfrA14-positive strains were clustered in a genetically related group including some dfrA1- and dfrA8-positive strains; meanwhile other genetic group included most of the dfrA8-positive strains. This distribution also correlated with the isolation period, showing a dynamics of trimethoprim genetic markers prevalent in Chilean S. sonnei strains. To our knowledge, dfrA14 gene associated to a small non-conjugative plasmid was detected for the first time in Shigella. Apparently, the strain causing the outbreak must have been introduced, changing drastically the genetic distribution of trimethoprim resistance in Chilean S. sonnei strains.